THE STATE OF TREE AND SHRUB VEGETATION IN THE YEREVAN SECTION OF THE HRAZDAN GORGE AND POSSIBILITIES FOR ITS IMPROVEMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The study of tree and shrub vegetation in the Yerevan section of the Hrazdan Gorge, covering an area of 276.8 ha, revealed the distribution patterns of native and introduced species, a critically low level of natural regeneration, widespread occurrence of pests and plant diseases, and the adverse effects of anthropogenic factors. During the research, a population of Alcea sophiae, a species listed as endangered in the Armenian Plants Red Book, was identified. The study proposes a comprehensive set of measures, including the control of invasive species, restoration of areals of native species, establishment of monitoring programs, and long-term ecosystem preservation to ensure biodiversity stability.
Keywords: tree and shrub vegetation; Hrazdan Gorge; invasive species; ecosystem; natural regeneration; monitoring; biodiversity